2021
DOI: 10.3390/jcm11010188
|View full text |Cite
|
Sign up to set email alerts
|

From Emotional (Dys)Regulation to Internet Addiction: A Mediation Model of Problematic Social Media Use among Italian Young Adults

Abstract: Internet addiction (IA) has mostly been investigated with the fear of missing out and difficulties in emotional regulation. The present study examined the link between IA and variables related to problematic social media use (i.e., fear of missing out, social media addiction), together with emotional (dys)regulation and personality traits, providing new insights and an integrated assessment of IA. In total, 397 participants, aged 18–35 years (M = 22.00; SD = 3.83), were administered a set of questionnaires per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 98 publications
0
23
0
Order By: Relevance
“…Individuals with emotional dysregulation are prone to risky and compulsive behaviors and maladaptive coping strategies for managing negative emotions ( Weiss et al, 2015 ). Emotion regulation plays a crucial role in internet addiction ( Mo et al, 2018 ; Quaglieri et al, 2022 ). Individuals with problematic internet use show difficulties in accepting negative emotions, controlling impulsive behaviors, and accessing effective emotion regulation strategies ( Pettorruso et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with emotional dysregulation are prone to risky and compulsive behaviors and maladaptive coping strategies for managing negative emotions ( Weiss et al, 2015 ). Emotion regulation plays a crucial role in internet addiction ( Mo et al, 2018 ; Quaglieri et al, 2022 ). Individuals with problematic internet use show difficulties in accepting negative emotions, controlling impulsive behaviors, and accessing effective emotion regulation strategies ( Pettorruso et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Solely, one study reported the association between addictive phone use and dysregulated eating and food addiction (17) . Positive relations between SM addiction and emotional dysregulation were observed previously (18,19) . Given the common phenomenon of altered eating behaviours serving as coping mechanisms among young adults, it is plausible that both SM addiction and heightened emotional appetite could be precipitated by emotional dysregulation and evolving coping strategies within this demographic.…”
Section: Discussionmentioning
confidence: 78%
“…Continuous communication using digital technology without time and space limitations creates a high risk of causing psychological problems. In a previous study, internet addiction in Italy was strongly associated with emotional regulation and dysregulation [ 24 ]. Problematic smartphone use can lead to fear of missing out (FoMO) and increase dependence and addiction.…”
Section: Introductionmentioning
confidence: 99%